Lack of Significant Association between Stromal Tumor-Infiltrating Lymphocytes and 2014 FIGO Stage in Epithelial Ovarian Cancer: A Cross-Sectional Study - Amanda Putri; Aswiyanti Asri; Puja Agung Antonius (JUXTA: Jurnal Ilmiah Mahasiswa Kedokteran Universitas Airlangga, 2026)
Highlights: Understanding the relationship between TIL infiltration and tumor stage could refine prognostic models and guide targeted therapies. Tumor-infiltrating lymphocytes density is considered an essential immune marker in ovarian cancer, but this study did not demonstrate a significant association with FIGO staging.   Abstract Introduction: Ovarian cancer is the fifth most common cancer among females. Prognostic factors such as stage and tumor-infiltrating lymphocytes (TILs) may influence outcomes. This study aimed to analyze the relationship between stromal TIL density and 2014 International Federation of Gynecology and Obstetrics (FIGO) staging in epithelial ovarian cancer. Methods: This cross-sectional analytical study included 44 cases (n=44) of epithelial ovarian cancer diagnosed at the Laboratory of Anatomical Pathology, Dr. M. Djamil General Hospital, Padang, Indonesia, in 2021-2022, selected using consecutive sampling. Stromal TIL density was evaluated on hematoxylin and eosin (HE) slides according to the International TILs Working Group guidelines and categorized as low (≤10%) or high (>10%). 2014 FIGO staging was obtained from medical records. Statistical analysis was performed using the International Business Machines Corporation (IBM) Statistical Package for the Social Sciences (SPSS) version 26.0, with Chi-square or Fisher’s exact test, and p<0.05 was considered significant. Results: Early-stage disease (stage I-II) comprised 25 cases (56.8%), of which 12 cases (48%) had low TIL density, and 13 cases (52%) had high TIL density. Advanced-stage disease (stage III-IV) comprised 19 cases (43.2%), of which 13 (68.4%) had low TIL density and 6 (31.6%) had high TIL density. Chi-square analysis showed no significant association between TIL density and FIGO stage (p=0.295). Conclusion: No significant relationship was found between stromal TIL density and 2014 FIGO staging in epithelial ovarian cancer. Further research with larger cohorts and detailed TIL subtypes may clarify their prognostic relevance.